Friction-stir welding of aluminium alloy 5083 - Klobčar, Damjan (Materiali in tehnologije, 2012)
A study was made of the weldability of 4-mm-thick aluminium-alloy 5083 plates using friction-stir welding. A plan of experiments was prepared based on the abilities of a universal milling machine, where the tool-rotation speed varied from 200 r/min to 1250 r/min, the welding speed from 71 mm/min to 450 mm/min and the tool tilt angle was held constant at 2. The factors feed per revolution (FPR) and revolution per feed (RPF) were introduced to get a better insight into the friction-stirring process. Samples for microstructure analyses, Vickers micro-hardness measurements and special miniature tensile-testing samples were prepared. The microstructure was prepared for observation on a light microscope under a polarised light source. A set of optimal welding parameters was determined at a FPR of 0.35 mm/r, at which quality welds can be made with a minimal increase in the weld hardness and an up to 15 % drop in the tensile strength.
Keywords: friction stir welding; varjenje s trenjem in mešanjem; mechanical properties; pločevina; mehanske lastnosti; welds; zvari